Knowledge, Attitude and Preventive Practices Regarding Dengue among Secondary School Students in Dharan, Nepal - Kandel, Suresh; Nath, Mahesh; Singh, Dhani; Chapagain, Krishna; Rauniyar, Rakesh; Tamang, Sapana; Banmali, Shreejana (Journal of College of Medical Sciences-Nepal, 2025)
Background Dengue fever, caused by the dengue virus and transmitted primarily by Aedes mosquitoes, is a significant public health concern in tropical and subtropical regions, with rising incidence rates in Nepal in recent years. This study aimed to assess the knowledge, attitudes, and preventive practices regarding dengue among secondary school students in Dharan, Nepal. Methods A descriptive cross-sectional study was conducted among secondary school students in Dharan. Data were collected using a structured self-administered questionnaire which were analyzed in SPSS version 16 to identify factors influencing knowledge, attitude and practices. The sample consisted of students from both public and private schools. Frequencies and percentages were used for the descriptive statistics while Chi-square test was used to test the association between variables. Results The study revealed significant gaps in dengue knowledge among students, despite the high prevalence of dengue within their families, with only 25.50% of the students having adequate knowledge. While most students displayed a positive attitude towards dengue prevention (95.50%), their preventive practices were found to be satisfactory (71.38%). Educational grade, religion and respondent’s mother’s educational status were found to be significantly associated with knowledge. Sex was found to be significantly associated with attitude and school type and house type were found to be significantly associated with preventive practices. Conclusions Secondary school students exhibited considerable gaps in dengue knowledge despite high familial exposure, although attitudes and preventive practices were generally positive. This highlights the need for targeted school-based health education programs to enhance awareness and preventive behaviors among students.